Pragmatic Meaning of Cigarette-Related Hoax on Social Media: Cyber-Pragmatic Study - Saragi, Devi Melisa (Universitas Cokroaminoto Palopo, 2024)
The relationship between hoaxes and the internet is really intricate and impactful. There are varieties of hoaxes spread in the internet. With their accelerated spread, ease of creation, virality, anonymity and pseudomity, hoaxes have easily provoked the public. As we know, hoaxes are described in such detail even the intrinsic function of language is not properly used. The language which is supposed to deliver ideas and communicate has been used improperly by irresponsible people who are tyring to deceive or cause concern and fear. Hence, this research aims at increasing the awarness of hoaxes on social media especially the hoax of cigarette related news by understanding the pragmatic meaning of cigarette hoaxes spread in internet. By implementing the cyber-pragmatics perspective, the writer tried to describe the virtual external context in order to find the meaning of the hoax utterances. Cyberpragmatics is an analysis of Internet-mediated communication from the perspective of cognitive pragmatics (Yus, 2011). The data were taken from social media, such as facebook, twitter, instagram, tiktok and online news by implementing the note taking technique. All data which have been gathered were then analyzed by distribution analysis method with forward expansion technique (Rahardi, 2020). From the analysis of the data, there are 8 meaning of cigarette –related hoaxes found as follow; 1. influencing ; 2. defaming; 3. satirizing; 4. propagandizing; 5. questioning; 6. spreading commotion; 7. validating and 8. harrassing. By this research, public is expected to increase the critical awareness toward hoaxes spread in the internet so that they just don’t accept all the information without any consideration.